Застосування штучного інтелекту для тестування програмного забезпечення - Шкурко, В. В. (ХНУРЕ, 2024)
This scientific article explores the burgeoning field of applying artificial intelligence (AI) to software testing, aiming to enhance the efficiency and effectiveness of the software development lifecycle. The study delves into the integration of AI techniques, including machine learning, natural language processing, and automation, to streamline testing processes and address the evolving challenges in software quality assurance.
Keywords: тестування програмного забезпечення; штучний інтелект